Evaluation of the pollution extent of heavy metals in the sediment of the Nile Delta, Mediterranean Coast, Egypt - Amani Badawi; Shaimaa M. Magdy (Egyptian Journal of Aquatic Research, 2023)
The Nile Delta coast extends along the middle region of Egypt’s Mediterranean coast, from Port Said eastward to Alexandria westward. Six short sediment cores were collected across the Nile Delta sector to assess the pollution level of nine heavy metals: Fe, Mn, Zn, Ni, Cu, Cr, Cd, Pb, and Ba. Geochemical analysis of the core samples revealed their sediment features. The predominant sediment was Nile fine-grained sand, with fluctuations in organic matter, carbonate, and heavy metal content. They correspond mainly to an exposure scale to effluent discharges, relevant to anthropogenic factors influencing the coastal ecosystem. The applied environmental indices demonstrated that the western and middle sites of the Nile Delta are classified as unpolluted areas, while the eastern edge, represented by the Port Said core, is identified as polluted area. Variations in the metal contamination level were recognized, ranging from high contamination with Cd to considerable contamination with Cr, and moderate contamination with Zn, Ni, Cu, Mn, and Fe. Port Said site is significantly affected by the anthropogenic impact of industries and port activities. It is recommended to mitigate ecological threats and limit pollution spreading westward to prevent further degradation of the Nile Delta coast.